Intracranial Part of Facial Nerve Along with its Clinical Implications - Singh, Rajani (Medical Science: Trends and Innovations Vol. 1, 2025)
The facial nerve, also known as the seventh cranial nerve, is comprised of motor and sensory roots. Both these roots of the facial nerve are attached to the ponto-medullary junction. The motor root innervates muscles of facial expression and the sensory part carries secretomotor fibers to lacrimal, submandibular and lacrimal glands and taste fibers to the anterior two third of the tongue. The facial nerve passes through the posterior cranial fossa and then through the temporal bone. It emerges out of the cranium through the stylomastoid foramen and passes through the parotid gland, ultimately innervating facial muscles. The facial nerve may be injured anywhere in its course in the cranium and in the extracranial course. If a facial nerve is injured, anywhere in its course, it leads to paralysis of facial muscles along with diminished secretion from the glands innervated by this nerve. In addition, there is a loss of taste sensation in the anterior two-thirds of the tongue leading to the helm of complications. The aim of this chapter is to highlight the intracranial course and related complications of the facial nerve. For this, various databases like Google Scholar, sciELO, PubMed etc articles and anatomical books were explored, and information is consolidated and presented in this chapter.